An observational study on the behavior of nurse on the delivery of oral health care to patients in a government tertiary hospitals in Manila - Barruga, Dave John Paul S.; Bringas, Hannah Patricia E.; Montenegro, Greame Cecilia C.; Ponce, Gladys Ann M.; Velasquez, Nicole Anne F. (Department of Community Dentistry, University of the Philippines Manila, 2018)
Introduction: Nurses are essential in promoting oral health in the hospital setting as they are the primary providers of oral health care for their patients. Although nurses have knowledge with oral health care, variations in terms of their practice in providing it are seen. This study determined how nurses in a government tertiary hospital in Manila practice their knowledge on oral health care for their patients, and what factors affect their provision of such care.